Does emotional intelligence mediates workplace stress, mindfulness, person-job-fit, and mental health among bank employees - Obinna Osita Ike; Ebele Evelyn Nnadozie; Elisha John Igwe (Frontiers in Psychology, 2026)
Introduction Mental health challenges among bank employees represent a growing public health concern with substantial individual and organizational consequences. Guided by the Job Demands–Resources (JD-R) model and Emotion Regulation Theory, this study examined the mediating role of emotional intelligence (EI) in the relationships between workplace stress, trait mindfulness, and person–job fit (PJF) on employee mental health in the banking sector. Methods Using a two-wave, time-lagged survey design, 412 bank employees (males = 159, 38.6%; females = 253, 61.4%; age range: 25–55 years; M = 35.64, SD = 7.30) were recruited from commercial banks in Southeast Nigeria via multi-stage sampling. Participants completed validated measures of workplace stress, mindfulness, person–job fit, emotional intelligence, and mental well-being. Data were analyzed using Hayes’ PROCESS macro (Model 4). Results Results indicated that mindfulness was negatively associated with mental health, whereas EI and PJF demonstrated significant positive associations. Workplace stress showed no significant direct relationship with mental health. With respect to direct pathways, mindfulness negatively predicted EI, while workplace stress demonstrated a positive association with EI; PJF showed no significant direct effect on EI. Notably, EI significantly mediated the mindfulness–mental health pathway, partially reducing the adverse direct effect of mindfulness on mental health — a finding that challenges the prevailing assumption that mindfulness is uniformly beneficial in occupational contexts. EI did not mediate the PJF–mental health or workplace stress–mental health pathways. Discussion These findings suggest that emotional intelligence (EI) serves as a psychological mechanism connecting mindfulness to employee mental health. This underscores the intricate and context-dependent nature of mindfulness, particularly in high-demand work environments such as the banking sector.